An expert system for transport mode selection for US medical supply chains based on data mining - Wang, Chenyu (2020)
It is easy to notice that the exposure of polluted environments, chronic diseases, and rising injury accidents contribute to the disease diversity and frequency among people, and the demands of medical supplies keep increasing around the world. Therefore, it is necessary to standardize and improve the medical supply chain system continuously. The transport mode selection, as a critical aspect in the medical supply chain system, has been concerns of many. There is evidence that the transport mode often influences the quality of products in supply chains, and the limited transport selection can lead to some potential risks. To guarantee serving customers with the high quality of medical supplies, the scientific transport mode selection system is necessary to be developed to contribute to providing decision-makers reasonable transport mode recommendations.